Reduce Anxiety Facing the Future of Women Victims of Domestic Violence Through Cognitive Restructuring Technical Group Guidance - Triyono, Triyono; Hidayati, Wahyu Nur (Universitas Negeri Malang, 2023)
This study aims to determine the effect of group guidance through cognitive restructuring techniques to reduce anxiety in facing the future of women victims of domestic violence. This research was conducted at SPEK-HAM Surakarta. This research is a pre-experimental study with a one-group pretest-posttest design. The subjects of this study were five women victims of domestic violence who had families, children, and anxiety about the future. This research was conducted in three meetings, providing material, discussion, question and answer, and ice-breaking. The data collection technique in this study is using an anxiety scale to obtain quantitative data. The interviews and observations were used to obtain qualitative data. The results showed decreased anxiety in facing the future from the initial condition before treatment. Based on hypothesis testing with non-parametric statistics using the Wilcoxon signed-rank test, the Z value obtained is -2.043 with a p-value (Asymp. Sig 2 tailed) of 0,042 where 0.0 less than 0.05, which indicates a significant difference between being given the action. Thus, the hypothesis that group counseling through cognitive restructuring techniques reduces anxiety facing the future of women victims of domestic violence is accepted.